Laporan Kasus : Anak Perempuan Usia 12 Tahun dengan Selulitis Preseptal - Nabila Fatimah Az-Zahra; Rani Himayani; Helmi Ismunandar (CV. Jasa Sukses Abadi, 2020)
One of the most common infections of the eyelid and periorbital soft tissues is preseptal cellulitis that is characterized by acute eyelid erythema and edema. Preseptal cellulitis are much more common in young children than adults. In addition, preseptal cellulitis is more frequent than orbital cellulitis. Preseptal cellulitis occurs anterior to the orbital septum. Preseptal cellulitis is a common infection of the eyelid and periorbital soft tissue that is characterized by acute erythema and edema of the eyelid.Most preseptal cellulitis is caused by local spread of sinusitis or adjacent dacryocystitis, external eye infection, or after trauma to the eyelidPreseptal cellulitis generally occurs in children rather than adults.Radiological examination such as imaging with MRI or CT is not indicated unless suspected orbital cellulitis or eyelid abscess is present, or there is a failure to respond to therapy.Administration of antibiotics in patients with preseptal cellulitis caused by bacterial infection must be started as soon as possible.This study discusses the case of girl with preseptal cellulitis who were treated with appropriate antibiotics.